Business Performance of Women-Owned SMEs in Malaysia: Learning and Entrepreneurial Orientations and The Mediating Roles of Competitive Advantage - Norshafizah, Hanafi (2012)
The aim of this study is to address the needs for research in the relationship between learning orientation (LO), entrepreneurial orientation (EO), competitive advantage (CA) and the performance of women-owned small and medium enterprises (SMEs) in Malaysia. A theoretical model based on a Resource Based View (RBV) approach to the business performance of SMEs was developed. To answer the research questions, six hypotheses were formulated. These are; (i) There is significant relationship between LO and performance, (ii) There is significant relationship between EO and performance, (iii) There is significant relationship between LO and CA, (iv) There is significant relationship between EO and CA, (v) CA mediates the relationship between LO and performance, and (vi) CA mediates the relationship between EO and performance. A quantitative survey method was employed in the study, and the questionnaires were used to obtain the data from the owner/managers of women owned SMEs. A total of 165 usable questionnaires were obtained from the survey, giving a response rate of 15.8 percent. Data were analysed using regressions to test the direct and indirect relationships. The findings indicate that the direct relationships between LO and EO to performance, and between LO and EO to competitive advantage were supported. The finding also confirms the mediating effect of CA on the relationship between LO and performance, while the mediating effect of CA on the EO- performance relationship was partially supported. More importantly, the results have demonstrated supportive evidence of the theoretical model of RBV, which provides an explanation on the relationships between LO, EO and CA, and how these variables affect performance of SMEs. The findings offered several theoretical and practical implications to owner/managers of women owned SMEs and also to the policy makers. The limitations of study and recommendations for future research were also addressed.